The challenge of setting restoration targets for macroalgal forests under climate changes. (15th January 2023) - Fabbrizzi, Erika; Giakoumi, Sylvaine; De Leo, Francesco; Tamburello, Laura; Chiarore, Antonia; Colletti, Alberto; Coppola, Marianna; Munari, Marco; Musco, Luigi; Rindi, Fabio; Rizzo, Lucia; Savinelli, Beatrice; et al.
Abstract: The process of site selection and spatial planning has received scarce attention in the scientific literature dealing with marine restoration, suggesting the need to better address how spatial planning tools could guide restoration interventions. In this study, for the first time, the consequences of adopting different restoration targets and criteria on spatial restoration prioritization have been assessed at a regional scale, including the consideration of climate changes. We applied the decision-support tool Marxan, widely used in systematic conservation planning on Mediterranean macroalgal forests. The loss of this habitat has been largely documented, with limited evidences of natural recovery. Spatial priorities were identified under six planning scenarios, considering three main restoration targets to reflect the objectives of the EU Biodiversity Strategy for 2030. Results show that the number of suitable sites for restoration is very limited at basin scale, and targets are only achieved when the recovery of 10% of regressing and extinct macroalgal forests is planned. Increasing targets translates into including unsuitable areas for restoration in Marxan solutions, amplifying the risk of ineffective interventions. Our analysis supports macroalgal forests restoration and provides guiding principles and criteria to strengthen the effectiveness of restoration actions across habitats. The constraints in finding suitable areas for restoration are discussed, and recommendations to guide planning to support future restoration interventions are also included. Highlights: Macroalgal forests are critical for the functioning of marine ecosystems. Spatial planning for marine ecosystem restoration has received scarce attention. We propose for the first time restoration targets and criteria for macroalgal forests. Six planning scenarios were developed to reflect the Biodiversity Strategy targets. Targets are only achieved when the recovery of 10% of macroalgal forests is planned.